Corporate governance of insurance firms after Sovency II - Michele Siri (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2017)
Under Solvency II, corporate governance requirements are a complementary, but nonetheless essential, element to build a sound regulatory framework for insurance undertakings, also to address risks not specifically mitigated by the sole solvency capital requirements. After recalling the provisions of the second pillar concerning the system of governance, the paper is devoted to highlight the emerging regulatory trends in the corporate governance of insurance firms. Among others, it signals the exceptional extension of the duties and responsibilities assigned to the Board of directors, far beyond the traditional role of both monitoring the chief executive officer, and assessing the overall direction and strategy of the business. However, a better risk governance is not necessarily built on narrow rule-based approaches to corporate governance.
Keywords: 330; Insurance; Corporate Governance; Board of Directors; Culture; Risk Management; Internal Controls; Principle of Proportionality; Regulation; EIOPA; Solvency; Guidelines